Real estate developer perception for sharia housing products in greater Bandung, Indonesia / Raden Aswin Rahadi …[et al.] - Rahadi, Raden Aswin; Majid, Rizky Nurul; Faturohman, Taufik; Hasanah, Eneng Nur; Rahmawati, Dwi (Universiti Teknologi MARA, 2021)
This research aims to define the sharia housing products from the perspective of real estate developers in Greater Bandung. The authors try to dig deeper into whether the housing made by these developers is by the fundamental understanding of sharia housing or not. This study also tries to determine what is still missing and what has been running well in practice. In the preliminary research, the authors attempted to define this sharia property by theories and more focused on the consumer side. This study is using Qualitative Analysis with Semi-Structured Interviews. From the result of this research, it can be seen that sharia housing in Bandung is not very focused on the design of sharia building in private residential, but rather to provide sharia facilities for public use and other Islamic activities in their neighbourhood. This research would be useful for property developers, consumers, and other parties like academicians or the government.